Method for manufacturing carboxymethyl cellulose particles, carboxymethyl cellulose particles manufactured thereby, and absorbent article comprising the same

JP2025024043AActive Publication Date: 2025-02-19LOTTE FINE CHEMICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024195879
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-03-04
Filing Date
2024-11-08
Publication Date
2025-02-19
Estimated Expiration
2040-03-04

AI Technical Summary

Benefits of technology

【0015】 本発明によると、コア架橋反応段階を経たCMC架橋体を表面架橋剤と反応させてコア -シェル構造を有するCMCを得る段階を含むことによって、高吸収性を有する改質され たCMC粒子が製造され得る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025024043000001_ABST
    Figure 2025024043000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing CMC particles having excellent blood absorbency, centrifuge retention capacity (CRC), and absorbency under load (AUL).SOLUTION: There are provided a method for manufacturing carboxymethyl cellulose particles, cellulose derivative particles manufactured by the method, and an absorbent article comprising same, wherein the method comprises: a step of reacting a cellulose raw material with an alkalizer to obtain alkalized cellulose; a step of reacting the alkalized cellulose with a carboxy methylating agent to obtain carboxymethyl cellulose; a primary cross-linking step of reacting the carboxymethyl cellulose with a core cross-linker to obtain a slurry-state carboxymethyl cellulose cross-linked body; a step of filtering the slurry-state carboxymethyl cellulose cross-linked body, followed by cleaning and dehydration; a secondary cross-linking step of reacting the carboxymethyl cellulose cross-linked body undergoing step with a surface cross-linker to obtain carboxymethyl cellulose having a core-shell structure; and a step of drying and pulverizing the carboxymethyl cellulose having a core-shell structure to obtain carboxymethyl cellulose particles having a core-shell structure.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to carboxymethyl cellulose. A method for producing CMC particles, and a method for producing CMC particles by said method More specifically, the present invention relates to a CMC crosslinked polymer having undergone a core crosslinking reaction step and an absorbent article including the same. A method for producing a CMC particle, comprising the step of reacting a CMC body with a surface cross-linking agent to obtain a CMC having a core-shell structure. The present invention relates to a method for producing CMC particles, CMC particles produced by said method, and absorbent articles containing the same. do. [Background technology]

[0002] Superabsorbent Polymer (hereinafter referred to as "SAP") (c) is a functional material that can absorb tens to thousands of times its own weight in water. Hygiene products such as diapers for use, feminine hygiene products such as sanitary napkins and adult urinary incontinence products, and bowel pads Pet supplies, medical absorbents, water-stopping materials for civil engineering and construction, seedling sheets and freshness in the food distribution field It is widely used as a material in absorbent articles such as a maintainance agent.

[0003] The SAP is mainly used for disposable purposes, so it is easy to manufacture and has a low unit price. It is necessary to determine the absorption force of water from the substrate containing the aqueous liquid, the liquid permeability, and the strength of the swollen gel. Physical properties such as the degree of adhesion are emphasized.

[0004] Conventionally, acrylic absorbent resins have been used as SAPs due to their high absorbency and low cost. However, acrylic absorbent resins are widely used due to their low cost. The resulting substance may be toxic due to residual monomers, so it is not suitable for use in diapers or sanitary products. However, when applied to skin, it has the disadvantage of inducing erythema and pruritus on areas of the body that come into contact with it for a long period of time. Therefore, we have produced highly absorbent particles using CMC derived from cellulose, a natural plant material. Therefore, research has been conducted into methods for applying the same to absorbent products.

[0005] As such a conventional method, Patent Document 1 (Korea Patent Publication No. 2001-010 No. 5311 (a) one or more polysaccharides containing acidic groups, such as CMC, (b) optionally cross-linking the polysaccharide with a cross-linking agent to form a gel; (c) adjusting the pH of the acidified polysaccharide to a value between 3.5 and 5.5; (d) crushing the gel; and (e) drying the crushed polysaccharide at an elevated temperature. A method for producing a highly absorbent polysaccharide derivative comprising the steps of:

[0006] The patent document 1 discloses that the highly absorbent polysaccharide derivative is a polysaccharide derivative having various salts and nonionic substances. The present invention can be used to absorb liquids, such as diapers, sanitary napkins, etc., which are composed of bodily fluids containing substances. The document states that the highly absorbent polyester is particularly suitable for the manufacture of such absorbent sanitary articles. Sugar derivatives are mainly used as absorbent materials in urine absorbing diapers. However, it has relatively low blood absorption, so it is not suitable for use in blood-absorbing feminine products. This is because the physical properties of urine and menstrual blood are very different. Blood contains water, salts, proteins, cells, etc., so it has a higher viscosity than urine. The diffusion rate is very slow. Also, large cell masses contained in blood are absorbed by the highly absorbent polymer. It is not absorbed by existing SAPs such as saccharide derivatives, but forms a film on the surface and absorbs blood. This prevents the

[0007] As a method for solving such a problem, Patent Document 2 (Japanese Unexamined Patent Publication No. 200 (i) providing an aqueous solution containing a polyvalent metal ion and a surfactant; (ii) adding a cellulose derivative and / or alginic acid or a salt thereof to the aqueous solution; (iii) a step of crosslinking the mixture, and then swelling and hydrating the mixture to form a gel; A step of contacting the crosslinked gel obtained by the step with a hydrophilic volatile solvent to dehydrate it; and iv) drying the absorbent. The method for producing the material comprises: Further comprising the step of treating with a cross-linking agent.

[0008] With reference to the examples of Patent Document 2, the cellulose derivative and / or alginic acid Alternatively, CMC powder is used as a salt thereof, and CMC is added to the aqueous solution provided by the step (i). The MC powder is added to the mixture, which swells and crosslinks the mixture to obtain a crosslinked gel. (ii) To obtain a gel, the CMC powder rapidly absorbs water and swells at the beginning of the process, resulting in a high viscosity. This can lead to a non-uniform crosslinking reaction. When considering the wearing comfort when applied to sanitary napkins and adult urinary incontinence products, It is necessary to improve the blood absorption and water retention capacity of the material. The absorbency measured by pressure, which measures the degree to which water is absorbed, is also a factor that can affect the wearing comfort. So there is a demand for improvement in this regard. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] KR1020010105311 A [Patent Document 2] JP2005263858A Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention is aimed at solving the above problems, and is directed to a CMC that has undergone a core crosslinking reaction step. The step of reacting the crosslinked body with a surface crosslinking agent to obtain a CMC having a core-shell structure is included. This improves blood absorption capacity and centrifuge retention capacity. Capacity, CRC) and Absorbency Under Load The object of the present invention is to provide a method for producing CMC particles with excellent properties (ad, AUL).

[0011] Another object of the present invention is to provide CMC particles produced by the above method and absorbent materials containing the same. The aim is to provide products that meet customer needs. [Means for solving the problem]

[0012] In one embodiment of the present invention, (1) a cellulose raw material is alkalized by reacting it with an alkalizing agent. (2) obtaining cellulose; and (3) reacting the alkalized cellulose with a carboxymethylating agent. (3) reacting the CMC with a core crosslinking agent to obtain a slurry of CMC; (4) A primary crosslinking step of obtaining a MC crosslinked body; and (5) filtering the CMC crosslinked body in the slurry state, (5) reacting the CMC crosslinked body obtained by the above (4) step with a surface crosslinking agent; (6) a secondary crosslinking step of crosslinking the core-shell CMC to obtain a CMC having a core-shell structure; and Drying and grinding the structured CMC to obtain CMC particles having a core-shell structure. The present invention provides a method for producing CMC particles comprising:

[0013] Another embodiment of the present invention provides CMC particles produced by the above-mentioned production method.

[0014] Another embodiment of the present invention is an absorbent material containing CMC particles manufactured by the above manufacturing method. Provide products. Effect of the Invention

[0015] According to the present invention, the CMC crosslinked body that has undergone the core crosslinking reaction step is reacted with a surface crosslinking agent to form a core. By including a step of obtaining a CMC having a shell structure, a modified CMC having high absorbency can be obtained. CMC particles can be produced.

[0016] The CMC particles thus produced have excellent gel strength and AUL due to surface crosslinking. It also has excellent blood absorption properties due to the increased volume density achieved through the secondary crosslinking step. Furthermore, according to the present invention, the water retention capacity measured under severe conditions, e.g. For example, we provide CMC particles with excellent CRC, which shows the amount of saline water retention measured after centrifugation. Therefore, the CMC particles according to the present invention are preferred for blood-absorbing feminine products. It can be used effectively.

[0017] In addition, according to the present invention, gelation of CMC does not proceed during the core crosslinking process, so that This can eliminate the problem of non-uniform crosslinking caused by high viscosity during the curing process. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a photograph of blood applied to the CMC particles prepared according to Example 1. [Diagram 2] FIG. 2 is a photograph of the Petri dish of FIG. 1 after the CMC particles that had not come into contact with blood had been shaken off. [Diagram 3] FIG. 3 is a photograph of blood applied to the CMC particles prepared in Example 8. [Figure 4] FIG. 4 is a photograph of the Petri dish of FIG. 3 after the CMC particles that had not come into contact with blood had been shaken off. [Diagram 5] FIG. 5 shows the apparatus for measuring the AUL of CMC particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present invention will now be described in detail.

[0020] In this specification, when a part "comprises" a certain component, this is unless specifically stated to the contrary. Unless otherwise stated, it is intended to include other elements rather than to exclude other elements. Taste.

[0021] As used herein, the term "core crosslinks" refers to crosslinks formed in the CMC backbone by reaction of the CMC with a crosslinking agent. The crosslinking agent used in this case is called the "core crosslinking agent" and is the same as the CMC. The reaction with the core crosslinker is called the "core crosslinking reaction."

[0022] As used herein, the term "surface crosslinking (or shell crosslinking)" refers to a CMC crosslinked body having a core crosslink. The term "crosslinking agent" refers to the crosslinking formed on the surface of the CMC crosslinked body by the reaction of the crosslinking agent. The crosslinking agent used is called a "surface crosslinking agent (or shell crosslinking agent)" and is used to crosslink the CMC crosslinked body and the surface The reaction with a crosslinking agent is called a "surface crosslinking reaction."

[0023] In one embodiment of the present invention, (1) a cellulose raw material is alkalized by reacting it with an alkalizing agent. (2) obtaining cellulose; and (3) reacting the alkalized cellulose with a carboxymethylating agent. (3) reacting the CMC with a core crosslinking agent to obtain a slurry of CMC; (4) A primary crosslinking step of obtaining a MC crosslinked body; and (5) filtering the CMC crosslinked body in the slurry state, (5) reacting the CMC crosslinked body obtained by the above (4) step with a surface crosslinking agent; (6) a secondary crosslinking step of crosslinking the core-shell CMC to obtain a CMC having a core-shell structure; and Drying and grinding the structured CMC to obtain CMC particles having a core-shell structure. The present invention provides a method for producing CMC particles comprising:

[0024] Hereinafter, the method for producing CMC particles according to the present invention will be described in detail step by step.

[0025] (1) The step of obtaining alkalized cellulose (alkalization reaction step)

[0026] In this step, the cellulose raw material is reacted with an alkalizing agent to obtain alkalized cellulose. It is a stage.

[0027] The cellulose raw material may be any of the usual pulps generally used in this field. There are no restrictions on the use of pulp, but specifically, pulp with a diameter of 1 μm or more and less than 8 mm is used. More specifically, pulp having a size of 0.15 mm or more and 0.5 mm or less can be used. Specifically, the cellulose raw material is raw cotton, linter, etc. 0.15% by weight of one or more pulps selected from the group consisting of wood and The cut pieces may be prepared by cutting them into pieces having a length of 0.5 mm or more. When using a cellulose raw material that has been treated, entanglement between the cellulose raw material and the mixer is reduced, and fine pulverization is achieved. Lump formation due to rubbing is suppressed, allowing for a uniform reaction and reducing work time. By ensuring workability and fluidity, productivity can be improved. This allows the product to be manufactured without going through a cutting process. It is possible to reduce manufacturing costs by more than 30% compared to using conventional cellulose raw materials.

[0028] The step of obtaining the alkalized cellulose can be carried out by a conventional method commonly used in the art. For example, after the cellulose raw material and the reaction solvent are charged into the reactor, Add an alkalizing agent and leave it at a temperature between 20℃ and 30℃ for 90 to 150 minutes. The cellulose is reacted with the aluminum alloy while stirring at a speed of 100 rpm to 200 rpm. Methods for conversion to potassium cellulose may be used.

[0029] The reaction solvent is water, acetone, isopropyl alcohol, etc. propyl alcohol, tert-butyl alcohol A group consisting of dimethyl ether and alcohol In this case, the amount of the reaction solvent used may be one or more selected from the following: The amount may be 50 parts by weight or more and 2,000 parts by weight or less per 100 parts by weight of the cellulose raw material. stomach.

[0030] The alkalizing agent is an alkali metal hydroxide. For example, the alkalizing agent can include sodium hydroxide. dium hydroxide, potassium hydroxide Lithium hydroxide and lithium hydride The alkalizing agent may contain one or more selected from the group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, The amount of the cellulose raw material is 5 parts by weight or more and 600 parts by weight or less relative to 100 parts by weight of the cellulose raw material. When the amount of the alkalizing agent added is within the above range, the catalyst may be easily removed in the step (2) described below. The carboxymethyl groups can be uniformly substituted throughout the cellulose, and the reaction of the carboxymethylating agent The reactivity is increased to obtain the CMC with the desired degree of substitution.

[0031] The purpose of adding the alkalizing agent is to weaken the crystal structure of cellulose, which will be described later. This is to allow the cellulose to easily react with the carboxymethylating agent. That is, the alkalizing agent promotes the reaction between the cellulose and the carboxymethylating agent. The cellulose that has been alkalized in this way is When the mixture is stirred in this state for a certain period of time, the crystal structure can be uniformly weakened.

[0032] (2) Step of obtaining CMC (carboxymethylation reaction step)

[0033] In this step, the alkalized cellulose obtained in the step (1) is treated with carboxymethylcellulose. This is the stage where CMC is obtained by reacting it with a vinylating agent.

[0034] The step of obtaining the CMC may be carried out by a conventional method commonly used in the art. For example, in a reactor containing the alkalized cellulose obtained by the step (1), A method in which a carboxymethylating agent is added and then the temperature is raised to carry out the reaction can be used.

[0035] According to one embodiment of the present invention, the step (2) is: (2-1) heating at 40° C. or more and 55° C. or less; a first carboxymethylation reaction step carried out for 90 minutes or more and 150 minutes or less; and (2-2) Secondary carboxymethylation reaction carried out at 65°C to 75°C for 30 to 90 minutes The steps may include:

[0036] Specifically, the carboxymethylating agent is chloroacetic acid. cid, sodium chloroacetic acid The reaction solution may include any one selected from the group consisting of ethyl alcohol, ... In this case, the reaction solvent may be water, acetone, or the like. Acetone, Isopropyl Alcohol ), tert-butyl alcohol and dimethyl and dimethyl ether. It is possible.

[0037] According to one embodiment of the present invention, the carboxylate of CMC prepared by the step (2) is The degree of substitution (DS) of the methyl group may be 0.7 or more and 2.0 or less, and the polymerization of the CMC may be The degree of polymerization (DP) may be 800 or more and 4,000 or less. The degree of substitution (DS) of carboxymethyl groups is the number of carboxymethyl groups per anhydroglucose unit in a cellulose molecule. The average number of hydroxyl groups substituted with carboxymethyl groups is defined as the average number of hydroxyl groups substituted with carboxymethyl groups. When the degree of substitution (DS) is within the above range, a uniform reaction can be carried out, which is preferable. The degree of polymerization of the CMC is a factor that affects the viscosity of the CMC, and the degree of polymerization is within the above range. In this case, it is preferable because CMC particles having excellent bulk density can be produced.

[0038] According to one embodiment of the present invention, before the step (3) described below, (2.5) the step (2) The neutralization step may further include a step of neutralizing the CMC obtained by the neutralization step. This can be carried out by conventional methods commonly used in the art, for example, by using CMC. A neutralizing agent is added to neutralize the mixture. Any oxidizing agent can be used as the neutralizing agent. For example, nitric acid, acetic acid, hydrochloric acid, etc. are mainly used, and these are 40% by weight or more and 99% by weight or less. It can be used in the form of an aqueous solution diluted to the following concentrations:

[0039] (3) Primary crosslinking step (core crosslinking reaction step)

[0040] In this step, the CMC obtained in step (2) is reacted with a core crosslinking agent to form a slurry. This is the stage where a CMC crosslinked body in a slurry state is obtained. Here, the slurry state means a high concentration of suspended solids. This means that the gel contains (CMC crosslinked body) and has low fluidity. The conversion does not proceed.

[0041] The steps (1) to (3) may be carried out continuously or discontinuously. When step (3) is carried out continuously in the same reactor, the reactor that has undergone step (2) contains There may be CMCs where the carboxymethylation reaction is complete or in progress, where the core crosslink In other words, according to the present invention, the above ( After step 2 (carboxymethylation reaction step), the wet (w The core crosslinking agent is added to the reactor containing the CMC in a wet state. The CMC in its original state can participate in the core crosslinking reaction to form a CMC crosslinked body. Through the reaction of the wet CMC with the core crosslinking agent, the core is bonded to the backbone of the CMC. Crosslinks are formed, and a crosslinked CMC body in a slurry state can be obtained.

[0042] On the other hand, when steps (1) to (3) are performed discontinuously, drying is performed after step (2). It can be crushed and pulverized, and the dry type CMC and the core crosslinker, as well as the reaction solvent, can be added to the reactor. Through the reaction of MC with the core crosslinker, a core crosslink is formed in the backbone of the CMC. This makes it possible to obtain a CMC crosslinked body in a slurry state.

[0043] In this case, it is more efficient to carry out the steps (1) to (3) continuously in the same reactor. This is preferable because the process is simpler and more economical than when it is carried out continuously. The cross-linked CMC ensures dispersibility and absorbency in 0.9% salt water. Cut.

[0044] According to one embodiment of the present invention, the core crosslinker is a mixture of an epoxy compound and a polyhydric alcohol. Specifically, the epoxy compound may include one or more selected from the group consisting of: Examples of epichlorohydrin and glycerol Diglycidyl ether (glycerol diglycidyl ether), poly Ethylene glycol diglycidyl ether diglycidyl ether), diethylene glycol diglycidyl ether (d iethylene glycol diglycidyl ether), ethylene glycol Ethylene glycol diglycidyl ether l ether), polypropylene glycol diglycidyl ether (polyprop ylene glycol diglycidyl ether), tripropylene glycol Coal diglycidyl ether (tripropylene glycol diglyc propyl ether), propylene glycol diglycidyl ether NE glycol diglycidyl ether), glycidol dol), and examples of the polyhydric alcohol include glycerin. in), glycerol, ethylene glycol glycol), diethylene glycol, triethylene glycol Ethylene glycol, tetraethylene glycol tetraethylene glycol, polyethylene glycol ethylene glycol), propylene glycol lycol, dipropylene glycol, poly Polypropylene glycol, etc. do.

[0045] According to one embodiment of the present invention, the content of the core crosslinking agent is 100 parts by weight of the cellulose raw material. The content of the core crosslinking agent may be 0.1 parts by weight or more and 40 parts by weight or less. When the crosslinking reaction efficiency is within the above range, the crosslinking reaction efficiency is excellent and the crosslinking density is appropriate. The centrifuge retention capacity of the CMC particles provided in the end on Capacity, CRC) can be improved.

[0046] According to one embodiment of the present invention, the step (3) is a heating process at 65° C. to 75° C. for 30 minutes or more. The stirring may be performed at a speed of 100 rpm to 300 rpm for a period of 90 minutes or less. When the reaction temperature, reaction time and stirring speed are within the above ranges, gelation does not proceed. In addition, the crosslinking reaction efficiency is high compared to the energy input. In addition, the step (3) is carried out under a pH condition of 6 to 8. In this case, the crosslinking reaction can be easily controlled and the efficiency of the crosslinking reaction can be improved.

[0047] (4) Filtration, washing and dehydration stage

[0048] In this step, the crosslinked CMC in a slurry state obtained in the step (3) was filtered. After that, the product is washed and dehydrated.

[0049] Specifically, the crosslinked CMC in a slurry state obtained in the step (3) is discharged from the reactor. After being discharged from the container, the container can be filtered by a conventional known filtering method. For example, For the purification, sieve filtration, suction filtration, ultrafiltration, filter press, etc. may be used. Specifically, suction filtration Filtration may be used, but is not limited to this.

[0050] According to one embodiment of the present invention, the washing step (4) is carried out using water and a hydrophilic volatile organic solvent. Specifically, one or more selected from the group consisting of hydrophilic volatile organic solvents may be used. The hydrophilic volatile organic solvent is not particularly limited, but may be an aqueous solution containing the hydrophilic volatile organic solvent. Typical examples are methanol, ethanol, and nor. n-propyl alcohol, isopropyl alcohol Isopropyl alcohol, normal butyl alcohol Isobutyl alcohol, Lower alcohols such as tert-butyl alcohol Coal; acetone, methyl ethyl ketone ketones such as 1,4-dioxane; Ethers such as tetrahydrofuran; N,N-dihydrofuran Amides such as methylformamide (N,N-dimethylformamide); Sulfoxides such as dimethyl sulfoxide and more specifically, methanol, ethanol, or isopropyl alcohol. Through the above cleaning process, impurities are removed and the CMC frame with a purity of 99% or more can be used. A bridge body can be obtained.

[0051] (5) Secondary cross-linking step (surface cross-linking reaction step)

[0052] In this step, the CMC crosslinked body obtained in step (4) is reacted with a surface crosslinking agent to form a core-shell crosslinked body. This is the stage where a CMC having a hexagonal structure is obtained.

[0053] According to one embodiment of the present invention, the surface crosslinking agent is a polyfunctional epoxy compound and a polyfunctional alko Specifically, the epoxidation agent may include one or more selected from the group consisting of epoxidation agents. Examples of compounds include epichlorohydrin, glycerol, glycerol diglycidyl ether, Polyethylene glycol diglycidyl ether l diglycidyl ether), diethylene glycol diglycidyl ether (diethylene glycol diglycidyl ether) Ethylene glycol diglycidyl ether dyl ether), polypropylene glycol diglycidyl ether (polypr Opylene glycol diglycidyl ether), tripropylene Glycol diglycidyl ether propylene glycol diglycidyl ether (propy lene glycol diglycidyl ether), glycidol (gly cidol, and examples of the polyhydric alcohol include glycerin. erin), glycerol, ethylene glycol e glycol), diethylene glycol, Triethylene glycol, tetraethylene glycol Tetraethylene glycol, polyethylene glycol (p olyethylene glycol), propylene glycol glycol), dipropylene glycol and polypropylene glycol. can be done.

[0054] According to one embodiment of the present invention, the content of the surface cross-linking agent is CMC having undergone the step (4). The amount may be 0.1 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the crosslinked body. When the content of the surface cross-linking agent is within the above range, the surface cross-linking reaction efficiency is excellent and the pressure absorption is good. It is possible to provide CMC particles having the ability to

[0055] Meanwhile, in the method for producing CMC particles according to the present invention, the step (5) is carried out by the following two methods: A selected one of the methods may be used.

[0056] As a first method, the step (5) is a step of forming a crosslinked CMC product obtained by the step (4) into a polymerizable mixture. Secondary crosslinking by reacting with a surface crosslinking agent and a foaming agent to obtain a porous CMC with a core-shell structure In this case, the foaming agent and the surface cross-linking agent are in a solution state and are reacted with the CMC cross-linking agent. Specifically, in the step (5), the CMC crosslinked body is reacted with the foaming agent solution and the surface. A surface cross-linking agent solution is poured in, or a mixed solution of a foaming agent solution and a surface cross-linking agent solution is poured in. can be inserted.

[0057] According to one embodiment of the present invention, the foaming agent may include a carbonate compound, Specifically, magnesium carbonate, calcium carbonate Calcium carbonate, sodium bicarbonate icarbonate and potassium bicarbonate The composition may contain one or more carbonate compounds selected from the group consisting of: The foaming agent may be introduced in the form of an aqueous solution as a water-soluble compound.

[0058] According to one embodiment of the present invention, the content of the foaming agent is the CMC crosslinked product obtained by the step (4). The amount may be 0.03 parts by weight or more and 20 parts by weight or less based on 100 parts by weight of the total weight. In particular, the content of the foaming agent may be 0.3 parts by weight or more and 15 parts by weight or less. When used in combination with other CMC particles, it is possible to provide CMC particles with excellent blood absorption capacity through improved bulk density. This can be done.

[0059] In the first method, the surface crosslinking agent solution contains a hydrophilic volatile organic solvent as a solvent. Examples of the hydrophilic volatile organic solvent include methanol. NOL, ethanol, normal propyl alcohol (n-prop Isopropyl alcohol, l), n-butyl alcohol, isobutyl alcohol Isobutyl alcohol, tert-butyl alcohol -butyl alcohol; acetone ketones such as methyl ethyl ketone; 1 ,4-dioxane, tetrahydrofuran Ethers such as N,N-dimethylformamide (N,N-dimethylformamide) dimethylsulfoxide; sulfoxide); and more specifically, alcohols, More specifically, the alcohol may be methanol, ethanol or isopropyl alcohol. It may be a ru.

[0060] According to one embodiment of the present invention, in the first method, the step (5) is Stir at 100 rpm to 300 rpm for 120 minutes to 270 minutes at 0°C or less. When the step (5) is carried out under the above reaction conditions, the CMC crosslinking The polymer, the foaming agent, and the surface cross-linking agent are uniformly distributed, so that the surface cross-linking efficiency can be improved.

[0061] In the second method, the step (5) is carried out by using the carboxymethyl cell that has been subjected to the step (4). A surface crosslinking agent solution prepared by dissolving the surface crosslinking agent in an organic solvent and water were added to the crosslinked cellulose. The carboxymethyl cellulose crosslinked body is surface-crosslinked and gelled at the same time, to form a core Even in the secondary crosslinking stage, carboxymethylcellulose in the gel phase with a shell structure is obtained. good.

[0062] According to one embodiment of the present invention, in the second method, the organic solvent has a boiling point lower than that of water. The solvent may include a hydrophilic volatile organic solvent having a low boiling point, specifically, an alcohol having a lower boiling point than water. Examples of the hydrophilic volatile organic solvent having a boiling point lower than that of water include methanol. methanol, ethanol, normal propyl alcohol (n-propyl alcohol), isopropyl alcohol alcohol), tert-butyl alcohol lower alcohols such as acetone; ketones such as tetrahydrofuran; Ethers such as tetrahydrofuran; Examples of alcohols with boiling points lower than that of water include methanol, ethanol, and isopropyl alcohol. Examples include alcohol.

[0063] According to one embodiment of the present invention, in the second method, the organic solvent added in step (5) is The content of the solvent is 200 parts by weight or more and 2,000 parts by weight or less based on 100 parts by weight of water. In the step (5) (surface cross-linking reaction step), the relative amounts of water and organic solvent are very Specifically, the amount of organic solvent is relatively large compared to the amount of water at the beginning of the surface crosslinking reaction. In this case, a rapid increase in viscosity due to CMC swelling can be suppressed, and this can lead to uniform surface crosslinking. Then, as the surface crosslinking reaction proceeds while the temperature is increased, the The amount of organic solvent may be relatively less than the amount of water, thereby forming a CM having the core bridge. As the surface crosslinking reaction of the C crosslinked body proceeds, the CMC crosslinked body swells and hydrates with water to form a gel. It can be made into

[0064] According to one embodiment of the present invention, in the second method, the step (5) is "adding an organic solvent The temperature was raised to 100°C or higher than the boiling point or the azeotropic point of water and the organic solvent for 120 minutes. The process includes stirring at a speed of 100 rpm to 300 rpm for a period of 360 minutes or more. When the step (5) is carried out under the above reaction conditions, the reaction proceeds in the later stage. Therefore, the organic solvent, which has a lower boiling point than water, may evaporate first. As the solution balance between organic solvent and water changes, a uniform surface crosslinking reaction proceeds and gelation occurs. In one example, when ethanol is used as the organic solvent, the azeotropic reaction between water and ethanol can be carried out. Below the temperature point (78.1°C), the solution balance becomes "amount of organic solvent > amount of water", and the azeotropic reaction gradually occurs. If the temperature is raised above this point, the amount of water may become greater than the amount of organic solvent. In the early stage of the process (amount of organic solvent > amount of water), a uniform surface crosslinking reaction mainly occurs, and the solution is dissolved by increasing the temperature. When the liquid balance changes (water volume > organic solvent volume), the surface cross-linking reaction gradually progresses and gelation proceeds. This allows the gelation to proceed smoothly while the surface crosslinking reaction proceeds uniformly. By using this method, CMC with excellent core-shell structure can be obtained. When CMC is crosslinked and gelled in the presence of dimethylformamide, the initial CMC swelling increases rapidly. The viscosity will increase, which may result in a non-uniform crosslinking reaction.

[0065] (6) Obtaining CMC particles

[0066] This step involves drying and annealing the CMC having a core-shell structure obtained in step (5). The step of crushing the mixture to obtain CMC particles having a core-shell structure. The shell-structured CMC can be dried and ground after undergoing a dehydration process.

[0067] The drying may be performed by any known drying method without limitation, for example, natural drying. , hot air drying or high temperature drying methods can be used.

[0068] The crushing can be carried out using a conventional crusher, for example, a cutting machine. Cutting mill, hammer mill, pin mill Pin mill, screw mill, roll mill A 1 / 2 mill, a disc mill, or the like may be used.

[0069] According to one embodiment of the present invention, the core-shell structure obtained by the step (6) is The bulk density of the CMC particles may be 0.5 g / ml or more and 0.9 g / ml or less, In the case of the above, particles having excellent blood absorption and dispersibility can be provided. When the range is included, when liquid is absorbed into an absorbent article containing the CMC particles, the particles The gel blocking phenomenon occurs when the gel particles rise to the upper layer of the absorbent article. Eliminates the problem of reduced initial absorbency caused by particles concentrating in the lower layer of the absorbent article It can be done.

[0070] The method for producing CMC particles according to the present invention is to prepare a core-shell CMC particle obtained by the step (6) The porous CMC particles with the structure are sieved to 85% or more in size of 150 μm or more. The size of the CMC particles may be further determined by a classification step to obtain particles having a size of 0 μm or less. When the grain size is within the above range, the grain size is small, so that the grain size is small and the grain size is small. The blockage phenomenon and excessive liquid permeability caused by large particle size lead to poor absorbency. When considering both dispersibility and absorbency, the size of the CMC particles is The diameter may be 250 μm or more and 500 μm or less.

[0071] Another embodiment of the present invention is a CMC particle manufactured by the above manufacturing method and a composition comprising the same. An absorbent article is provided.

[0072] According to one embodiment of the present invention, the blood absorption of the CMC particles is calculated by the following formula: The capacity may be 130 mg or more and 155 mg or less.

[0073] Calculation formula 1 Blood absorption capacity (mg) = W 2 -W 1

[0074] In the above formula 1, W 1 is the weight of the Petri dish, and W 2 The 1.0 g of CMC particles was After uniformly distributing the blood in the Petri dish, 0.1 ml of blood was placed in the center of the dish containing the CMC particles. Drop the blood one drop at a time and allow it to clot at room temperature for 2 hours. The weight of the Petri dish was measured after shaking off all the clean CMC particles that had been removed.

[0075] Thus, the CMC particles produced by the present invention have excellent AUL, CRC and blood Because of its absorbent ability, it is preferably used for female sanitary napkins, which are feminine products for absorbing blood. In addition, disposable diapers, adult urinary incontinence products, and other hygiene products and defecation masks are also available. It is possible to manufacture absorbent articles selected from the group consisting of pet dog products such as pet beds, and medical products. Materials such as absorbents, waterproofing materials for civil engineering and construction, seedling raising sheets, and freshness maintaining agents in the food distribution field It can also be used in a variety of ways. EXAMPLES

[0076] The present invention will be described in more detail with reference to the following examples. The examples are not limiting.

[0077] Example 1 First, pulp (Rayonier, Ethenier-F) was cut into pieces with a diameter of 0.15 mm or more. The cellulose raw material was prepared by cutting it to a length of less than 0.5 mm.

[0078] Then, the mixture was placed in a pressure reactor (Lodige, Druvatherm series). 90 g of the cut cellulose raw material was added and 80% by weight of the reaction solvent, isopropyl alcohol, was added. After adding 1231g of alcoholic water solution, 50% by weight of sodium hydroxide, which is an alkalizing agent, was added. The mixture was reacted at 25°C for 120 minutes with stirring at 150 rpm. Thus, alkalized cellulose was obtained.

[0079] Then, the reactor was charged with 45% by weight of sodium chloroacetate, which is a carboxymethylating agent. 360 g of the aqueous solution was added to produce CMC. Alkalized cellulose and carboxymethylating agent were mixed at 50°C for 120 min at 200 rpm. After the first carboxymethylation reaction step, the mixture is stirred at 70°C. It was produced through a secondary carboxymethylation reaction step that was reacted for 60 minutes. The degree of substitution (DS) of the carboxymethyl group of the CMC was 1.0, and the degree of polymerization (DP) was was 1,400.

[0080] Then, the core crosslinker, glycerol diglycidyl ether, was added to the reactor containing the CMC. Add 4 g of tert-butyl ether and perform the core crosslinking reaction ( A first crosslinking reaction was carried out to produce a crosslinked CMC in a slurry state. The MC crosslinked body does not undergo gelation.

[0081] Then, the slurry-state CMC crosslinked body is discharged from the reactor and passed through a suction filter (LKLa After filtering through a filter (Korea WJ-110), 900 ml of 70% ethanol solution was added. g was added for the first wash, and 900 g of an 80 wt % ethanol aqueous solution was added for the second wash. I was dehydrated after that.

[0082] Then, 30 g of the CMC crosslinked body that had been subjected to the dehydration process was transferred again to the pressure reactor, where 1 % by weight polyethylene glycol diglycidyl ether solution (solvent: ethanol) 270 0.45 g of sodium bicarbonate (foaming agent) dissolved in 90 g of water to prepare a foaming agent solution of 90 g. After adding 0.45g, the internal temperature of the reactor was raised to 70°C, and then it was heated at 70°C for 180 minutes. While stirring at a speed of 150 rpm, the surface cross-linking reaction (secondary cross-linking reaction) is carried out. A porous CMC with a cell structure was produced.

[0083] After the surface cross-linking reaction is completed, the porous CMC having a core-shell structure is removed. After washing with water and drying with hot air at 70°C for 360 minutes, the pieces were cut into pieces using a cutting mill (Fritsch, p ulverisette 19) to obtain porous CMC particles with a core-shell structure. In this case, the particle 1 had a diameter of 50 μm or more. The particle size of the particle 1 is in the range of 60 mesh (250 μm or less). The mixture was sieved through a standard sieve of 35 mm to obtain particles having a size of 250 μm or more. Particles with a size exceeding 500 μm when sieved through a standard mesh (500 μm) sieve are It was acquired through the method of elimination.

[0084] Example 2 A foaming agent aqueous solution 9 was prepared by dissolving 0.09 g of sodium bicarbonate (foaming agent) in 90 g of water. A core-shell structured C was prepared in the same manner as in Example 1, except that 0.09 g of the C MC particles (hereinafter referred to as "particles 2") were produced.

[0085] Example 3 A foaming agent aqueous solution 9 was prepared by dissolving 0.27 g of sodium bicarbonate (foaming agent) in 90 g of water. A core-shell structured C was prepared in the same manner as in Example 1, except that 0.27 g of the C MC particles (hereinafter referred to as "particles 3") were produced.

[0086] Example 4 0.9 g of the sodium bicarbonate (foaming agent) was dissolved in 90 g of water to obtain a foaming agent aqueous solution 90%. The same method as in Example 1 was used, except that 0.9 g of CMC having a core-shell structure was added. Particles (hereinafter referred to as "particles 4") were produced.

[0087] Example 5 A foaming agent solution 94 obtained by dissolving 4.5 g of sodium bicarbonate (foaming agent) in 90 g of water The same method as in Example 1 was used, except that 0.5 g of CMC particles having a core-shell structure were added. A particle (hereinafter referred to as "particle 5") was produced.

[0088] Example 6 The core was prepared in the same manner as in Example 1, except that the surface crosslinking reaction time was adjusted to 240 minutes. -CMC particles having a shell structure (hereinafter referred to as "particles 6") were produced.

[0089] Example 7 The same as in Example 1, except that the secondary carboxymethylation reaction time was adjusted to 80 minutes. CMC particles having a core-shell structure (hereinafter referred to as "particles 7") were produced by the method described above.

[0090] Example 8 C in a slurry state in which gelation did not occur, discharged from the reactor in Example 1 The MC crosslinked body was filtered, washed and dehydrated in the same manner as in Example 1.

[0091] Then, 30 g of the CMC crosslinked body that had been subjected to the dehydration process was transferred again to the pressure reactor, where 1 % by weight polyethylene glycol diglycidyl ether solution (solvent: ethanol) 270 After adding 90 g of ethanol and 90 g of water, the internal temperature of the reactor was raised to 88° C. for 240 minutes (15 Stir at a speed of 100 rpm to proceed with the surface crosslinking reaction (secondary crosslinking reaction) and gelation at the same time. A gel-phase CMC having an earth-shell structure was prepared. The azeotropic point of the solvent, ethanol and water, is 78.1°C. When the amount of ethanol is greater than the amount of water and the temperature is raised above the azeotropic point, the solution balance is changed. The amount of ethanol is less than the amount of water.

[0092] After the surface cross-linking reaction was completed, the CMC of the gel phase was adjusted to the same value as in Example 1. The core-shell structure is dehydrated, dried with hot air, and crushed into 250μm or more 500μm. CMC particles of submicron size (hereinafter referred to as "particles 8") were produced.

[0093] Example 9 In the surface crosslinking reaction (secondary crosslinking reaction), the internal temperature of the reactor was raised to 88°C for 3 Stir at 150 rpm for 00 minutes to cause surface crosslinking reaction (secondary crosslinking reaction) and gelation at the same time. The same procedure as in Example 8 was repeated, except that a gel phase CMC having a core-shell structure was produced. Using the same method, CMC particles having a core-shell structure (hereinafter referred to as "particle 9") were prepared. Ta.

[0094] Example 10 After producing CMC through the first and second carboxymethylation reaction steps, the core crosslinking reaction ( Before proceeding with the first crosslinking reaction, the temperature of the reactor containing the CMC was cooled to 30°C. Then, slowly add 60 ml of 35% HCl solution over 20 minutes to adjust the pH to 8.5. CMC particles having a core-shell structure were prepared in the same manner as in Example 8, except that the CMC particles were neutralized with (hereinafter referred to as "particle 10") was produced.

[0095] Comparative Example 1 The same procedure as in Example 1 was repeated except that 90 g of water without a foaming agent was added instead of the foaming agent aqueous solution. Using the same method, CMC particles having a core-shell structure (hereinafter referred to as "particle 11") were prepared. did.

[0096] Comparative Example 2 The core was crosslinked in the same manner as in Comparative Example 1, except that the surface crosslinking reaction time was adjusted to 240 minutes. -CMC particles having a shell structure (hereinafter referred to as "particle 12") were produced.

[0097] Comparative Example 3 The same as Comparative Example 1, except that the secondary carboxymethylation reaction time was adjusted to 80 minutes. CMC particles having a core-shell structure (hereinafter referred to as "particles 13") were produced by the method described above. .

[0098] Comparative Example 4 The CMC crosslinked body in a slurry state discharged from the reactor in Example 8 was After filtering, washing and dehydrating in the same manner as in 8, add water and mix to obtain CMC crosslinked polymer. In this case, the amount of water added was 100% of the slurry state after the dehydration process. The amount is 1,000 parts by weight based on 100 parts by weight of the CMC crosslinked body.

[0099] The CMC crosslinked body was then kneaded and formed into a sphere with a diameter of 2 cm, and then placed in an oven. After drying at 70°C for 360 minutes, the mixture was milled using a cutting mill (Fritsch Pulver The granules were pulverized using an Isette 19) to produce a granular CMC crosslinked body. The crosslinked CMC has a particle size ranging from 250 μm to 500 μm, and the core crosslink It has

[0100] Thereafter, 30 g of the granular CMC crosslinked body was transferred again to the pressure reactor, where the surface crosslinking The agent solution was a 1% by weight polyethylene glycol diglycidyl ether solution (solvent: ethanol). After adding 270 g of ethanol and 90 g of water, the surface crosslinking reaction was carried out by immersion. The surface cross-linking reaction temperature is 70°C and the reaction time is 1,440 minutes. The immersion method is a method in which the CMC crosslinked material is mixed with the polyethylene glycol diglycidyl ether without a stirring process. This refers to a method in which surface crosslinking is carried out while immersed in an ether solution or water.

[0101] After the surface cross-linking reaction was completed, the core was dehydrated, dried and pulverized in the same manner as in Example 8. -CMC particles having a shell structure (hereinafter referred to as "particle 14") were produced.

[0102] Comparative Example 5 The cellulose raw material used is uncut pulp (length 8 mm or more); The reaction time for the first carboxymethylation step was adjusted to 180 minutes, and the reaction time for the second carboxymethylation step was adjusted to 180 minutes. The core was prepared in the same manner as in Comparative Example 4, except that the reaction time of the polymerization step was adjusted to 120 minutes. CMC particles having a shell structure (hereinafter referred to as "particles 15") were produced.

[0103] Comparative Example 6 The cellulose raw material used is uncut pulp (length 8 mm or more); The reaction time for the first carboxymethylation step was adjusted to 180 minutes, and the reaction time for the second carboxymethylation step was adjusted to 180 minutes. The core crosslinking was carried out in the same manner as in Comparative Example 4, except that the reaction time in the polymerization step was adjusted to 120 minutes. A crosslinked CMC body with core crosslinks was produced through crosslinking reaction, washing and dehydration processes.

[0104] Then, the CMC crosslinked body that had undergone the dehydration process was immediately heated at 70°C for 36 h without a surface crosslinking reaction step. After drying with hot air for 10 minutes, the plate was cut into pieces using a cutting mill (Fritsch Pulveriset te 19) to obtain CMC particles having only core crosslinks (hereinafter referred to as “particle 16”). ) was manufactured.

[0105] <Evaluation method> 1. Blood absorption capacity Blood absorption capacity of particles 1 to 16 obtained in Examples 1 to 10 and Comparative Examples 1 to 6, respectively was evaluated as follows:

[0106] First, the weight (W) of a Petri dish with an inner diameter of 3 cm is 1 ) and add 1. After adding 0 g of particles, tap the bottom lightly to distribute the particles evenly over the surface of the dish. 0.1 ml of blood was placed in a 1 ml plastic syringe and a 21 G needle was inserted. Using a centrifuge, slowly drop one drop at a time onto the center of the particles in the Petri dish. Horse blood was used as the blood. The blood was then allowed to coagulate at room temperature for 2 hours. After that, shake off all clean particles that have not come into contact with blood, and separate the clotted blood and The weight of the Petri dish with the agglomerated particles remaining (W 2 ) was measured. The blood absorption capacity was calculated using the weight measured by the following formula (1), and the results are shown in Table 1 below. It was written.

[0107] Blood absorption capacity (mg) = W 2 -W 1 (1)

[0108] In the above formula (1), W 1 is the weight of the empty Petri dish, and W 2 The blood is clotted and This is the weight of the Petri dish containing the agglomerated particles.

[0109] Specifically, FIG. 1 shows a photograph of blood applied to the CMC particles prepared in Example 1. FIG. 2 shows the state after shaking off the CMC particles that were not exposed to blood from the Petri dish shown in FIG. 1. 3 shows a photograph of the CMC particles produced in Example 8 after applying blood to them. FIG. 4 shows a photograph of the CMC particles shaken off from the Petri dish of FIG. 3 that was not exposed to blood. The photo after the procedure is shown below.

[0110] 2. Absorbency Under Load (AUL) Pressure absorption capacity of particles 1 to 16 obtained in Examples 1 to 10 and Comparative Examples 1 to 6, respectively was measured using an apparatus as shown in FIG.

[0111] First, a cylindrical PMMA (polymethyl methacrylate) cylinder A 400 mesh metal mesh 5 is attached to the bottom of the hopper 7 (inner diameter: 60 mm, height: 50 mm). The particles 6 were attached to the metal mesh 5 at room temperature in an amount of 0.9 g (W 3 ) evenly and A plastic piston 8 with a 0.7 psi metal weight 9 is placed on top of the piston to measure the AUL. The device was configured.

[0112] Then, a porosity test was performed on the inside of Petri dish 1 (diameter: 118 mm, height: 12 mm). Place the #0 glass ceramic filter plate 2 (diameter: 80 mm, thickness: 7 mm). Then, physiological saline 3 composed of 0.9% by weight of sodium chloride aqueous solution is added to the ceramic. After inserting the ceramic filter so that it is flush with the mix filter plate 2, A filter paper 4 was placed on the filter plate 2 .

[0113] Then, the AUL measurement device was placed on the filter paper 4, and physiological saline was poured under pressure for 60 minutes. After absorption, the weight of the particles in the measuring device (W 4 ) was measured. The weight was used to calculate the AUL according to the following formula (2), and the results were listed in Table 1 below. .

[0114] AUL(g / g)=(W 4 -W 3 ) / W 3 (2)

[0115] In the above formula (2), W 3 is the weight of the initial particle (0.9g), and W 4 is the pressure (0.7 The weight of the particles after absorbing saline for 60 minutes under 100 psi.

[0116] 3.Centrifuge Retention Capacity CRC) The particles 1 to 16 obtained in Examples 1 to 10 and Comparative Examples 1 to 6 were centrifuged and stored. The water activity was measured as follows.

[0117] 0.2 g of each of the above particles (W 5 ) into a tea bag, seal it, and then store at room temperature for 0.9 The specimen was immersed in physiological saline consisting of a 50% by weight aqueous solution of sodium chloride for 30 minutes. The sealed tea bags are dehydrated using a centrifugal separator at 250G for 3 minutes, The weight of the sealed tea bag (W 6 ) was measured. The bag was subjected to the same immersion and centrifugation procedures, and its weight (W 7 ) is measured Using the weight thus measured, the CRC was calculated according to the following formula (3), The results are shown in Table 1 below.

[0118] CRC(g / g)=(W 6 -W 7 -W 5 ) / W 5 (3)

[0119] In the above formula (3), W 5 is the weight of the initial particle (0.2g), and W 6 Put the particles is the weight of the sealed tea bag after soaking and centrifugation, W 7 is a particle-free tee. - Weight of the bag after immersion and centrifugation.

[0120] [Table 1]

[0121] Referring to Table 1, in the case of particles 1 to 10 prepared according to Examples 1 to 10, Compared with particles 11 to 16 produced in Examples 1 to 6, the AUL, CRC and blood absorption capacity are superior. It was confirmed that the blood absorption capacity was particularly excellent. The embodiments disclosed in the present invention are not intended to limit the technical concept of the present invention. The scope of the invention is defined by the following claims. The present invention is not limited to the above-mentioned technical concepts, and all technical ideas within the scope of the present invention are within the scope of the present invention. must be construed as including [Explanation of symbols]

[0122] 1: Petri dish 2: Ceramic filter plate 3: Saline (NaCl solution) 4: Filter paper 5: Metal mesh 6: Superabsorbent particles 7: PMMA cylinder 8: Plastic piston 9: Metal weight

Claims

1. (1) reacting a cellulose raw material with an alkalizing agent to obtain alkalized cellulose; (2) reacting the alkalized cellulose with a carboxymethylating agent to obtain carboxymethyl cellulose; (3) a primary crosslinking step of reacting the carboxymethyl cellulose with a core crosslinking agent to obtain a carboxymethyl cellulose crosslinked body in a slurry state; (4) filtering the carboxymethyl cellulose crosslinked body in the slurry state, and then washing and dehydrating the same; (5) a secondary crosslinking step of reacting the carboxymethylcellulose crosslinked product obtained in step (4) with a surface crosslinking agent and a foaming agent to obtain a porous carboxymethylcellulose having a core-shell structure; and (6) A method for producing carboxymethylcellulose particles, comprising the step of drying and pulverizing the carboxymethylcellulose having a core-shell structure to obtain carboxymethylcellulose particles having a core-shell structure.

2. 2. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the cellulose raw material is prepared by cutting at least one pulp selected from the group consisting of raw cotton, linter, and wood to a length of 0.15 mm to 0.5 mm.

3. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the step (2) includes: (2-1) a first carboxymethylation reaction step carried out at 40° C. to 55° C. for 90 to 150 minutes; and (2-2) a second carboxymethylation reaction step carried out at 65° C. to 75° C. for 30 to 90 minutes.

4. 2. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the degree of substitution (DS) of the carboxymethyl group of the carboxymethyl cellulose produced by step (2) is 0.7 to 2.0, and the degree of polymerization (DP) of the carboxymethyl cellulose is 800 to 4,000.

5. The method for producing carboxymethyl cellulose particles according to claim 1, further comprising the step of neutralizing the carboxymethyl cellulose obtained by the step (2) before the step (3).

6. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the core crosslinking agent comprises at least one selected from the group consisting of epoxy compounds and polyhydric alcohols.

7. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the content of the core crosslinking agent is 0.1 to 40 parts by weight based on 100 parts by weight of the cellulose raw material.

8. The method of claim 1, wherein the step (3) is carried out at 65° C. to 75° C. for 30 to 90 minutes while stirring at a speed of 100 rpm to 300 rpm.

9. 2. The method of claim 1, wherein in step (4), the washing is performed using at least one selected from the group consisting of water and hydrophilic volatile organic solvents.

10. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the surface cross-linking agent comprises at least one selected from the group consisting of polyfunctional epoxy compounds and polyhydric alcohols.

11. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the content of the surface crosslinking agent is 0.1 to 40 parts by weight based on 100 parts by weight of the carboxymethyl cellulose crosslinked product obtained in step (4).

12. 2. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the foaming agent comprises at least one carbonate compound selected from the group consisting of magnesium carbonate, calcium carbonate, sodium bicarbonate, and potassium bicarbonate.

13. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the content of the foaming agent is 0.03 parts by weight to 20 parts by weight based on 100 parts by weight of the carboxymethyl cellulose crosslinked product obtained in step (4).

14. The method for preparing carboxymethyl cellulose particles according to claim 1, wherein the step (5) is carried out at 50° C. to 90° C. for 120 to 270 minutes while stirring at a speed of 100 rpm to 300 rpm.

15. 2. The method for producing carboxymethyl cellulose particles according to claim 1, wherein the volume density of the carboxymethyl cellulose particles obtained by step (6) is 0.5 g / ml to 0.9 g / ml.

16. Carboxymethyl cellulose particles, characterized by being produced by the production method according to any one of claims 1 to 15.

17. The carboxymethylcellulose particles according to claim 16, characterized in that the blood absorption capacity of the carboxymethylcellulose particles calculated by the following calculation formula 1 is 130 mg or more and 155 mg or less: Calculation formula 1 Blood absorption capacity (mg) = W 2 -W 1 In the above formula 1, W 1 is the weight of the Petri dish, and W 2 is the weight of the Petri dish measured by uniformly placing 1.0 g of carboxymethylcellulose particles in the Petri dish, continuously dropping 0.1 ml of blood drop by drop onto the center of the dish containing the carboxymethylcellulose particles, allowing the blood to clot at room temperature for 2 hours, and then shaking off all the clean carboxymethylcellulose particles that were not in contact with the blood.

18. An absorbent article comprising carboxymethyl cellulose particles produced by the method according to any one of claims 1 to 15.

Citation Information

Patent Citations

  • Water absorbing material, method for producing the same and water absorbing article

    JP2005263858A

  • Acidic superabsorbent polysaccharides

    KR1020010105311A